Pengaruh Perilaku Kewirausahaan dan Karakteristik Individu terhadap Keberhasilan UMKM di Pasar Tradisional - Putera B, Arsandy; Lestari, Indawati (Economics, Business and Management Science Journal, 2025)
The success of micro, small, and medium enterprises (MSMEs) does not only depend on profitability but also on entrepreneurial behavior and individual characteristics owned by business actors. This study aims to analyze the influence of these two factors on the success of MSMEs in the Sei Sikambing Traditional Market in Medan. The research method used was quantitative with a multiple linear regression approach, involving 55 traders as a sample. Data was collected through observations, questionnaires, and interviews, then analyzed using SPSS. The results showed that entrepreneurial behavior and individual characteristics simultaneously had a positive and significant effect on business success, with a contribution of 46.2%, while 53.8% was influenced by other factors. Individual characteristics such as tenacity, creativity, and adaptability have been proven to increase the competitiveness of MSMEs. Therefore, MSME actors need to improve their entrepreneurial skills and optimize individual characteristics to face increasing competitive market competition, especially in the era of digitalization.